Analisis Terhadap Politik Hukum Pengaturan Hubungan Industrial Di Indonesia (Studi Berdasarkan Peraturan Pengganti Undang-Undang (Perpu) Nomor 2 Tahun 2022 Tentang Cipta Kerja) - Wahyu Prianto (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2023)
This article looks at the legal politics used by the Indonesian government in regulating industrial relations by issuing government regulations in lieu of Law Number 02 of 2022 concerning Job Creation, using normative research methods that the law provides for regulation of industrial relations while also determining how or the road and whether the road can realize social protection and welfare. observation with the parties involved in order to obtain data information about the subjects and objects studied. The results of the research show that the legal politics used by the Indonesian government in regulating industrial relations by issuing government regulations in lieu of Law Number 02 of 2022 concerning Job Creation, the provisions on job creation, the Government is more inclined towards economic safety rather than protecting the interests of people seeking work, this can be seen with the widest possible space for entrepreneurs to be surveyed, and this is tied to the view that if entrepreneurs are healthy then the economy will improve, and if the economy improves then the lives of the Indonesian people will become prosperous, of course this is a big question as to whether the legal politics that are applied in industrial relations arrangements is true. Keywords: Legal Politics, Industrial Relations, Regulation